Oxygen chloride-based solid electrolyte material and solid-state battery

By adopting the general structural formula A2-2xZr1-xM2xCl6-6xO3x of the oxychloride-based solid electrolyte material and the metal oxide double-doping strategy, the ionic conductivity deficiency and compatibility of the existing lithium and sodium ion halide-based solid electrolytes are solved. Solve the problem of poor performance and achieve solid-state battery electrolyte materials with high ionic conductivity and (electro)chemical stability.

CN119361807APending Publication Date: 2025-01-24UNIV OF SCI & TECH BEIJING

Patent Information

Application Number
CN202411431999.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-14
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The existing lithium and sodium ion halide-based solid electrolytes face problems such as insufficient ionic conductivity, poor compatibility with alkali metal negative electrodes, and easy water absorption and dehydration, which seriously limit their application in solid-state batteries.

Method used

The structure of the structure of oxide-based solid electrolyte material A2-2XZR1-XM2XCL6-6xo3x is used to prepare a high ion conductivity, stable and compatible solid electrolyte with alkaline metal negative interface interface with metal metal negative interface Essence

Benefits of technology

An alkali metal ion oxychloride-based solid electrolyte with high ionic conductivity, good (electro)chemical stability and low price was achieved, effectively improving the electrochemical performance of solid-state lithium and sodium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119361807A_ABST
    Figure CN119361807A_ABST
Patent Text Reader

Abstract

The invention discloses an alkali metal ion oxychloride-based solid electrolyte material and a solid-state battery, and belongs to the technical field of solid electrolyte. The chemical general formula of the solid electrolyte material provided by the invention is A < 2-2x > Zr < 1-x > M < 2x > Cl < 6-6x > O < 3x >, wherein A is an alkali metal element Li or Na; m is metal or lanthanide elements of In, Bi, Sb, Ce and La; x is more than 0 and less than or equal to 0.3. The oxychloride-based solid electrolyte is prepared by the following preparation method: respectively weighing precursor ACl, ZrCl4 and M2O3 (A = Li and Na, and M = In, Bi, Sb, Ce and La) powder materials according to the stoichiometric ratio of a general formula, and carrying out one-step high-speed ball milling, so as to prepare target solid electrolyte powder; the method is applied to solid-state batteries. The alkali metal ion oxychloride-based solid electrolyte shows the advantages of high ionic conductivity, wide electrochemical window, air stability, good deformability and the like in a solid-state battery, and has the advantages of low cost, simple synthesis process, easiness in condition control and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of solid electrolytes, and in particular relates to an oxychloride-based solid electrolyte material and a solid-state battery. Background Art

[0002] At present, traditional commercial lithium-ion batteries (LIBs) and sodium-ion batteries (NIBs) that rely on organic liquid electrolyte systems have risks such as flammable, easy leakage and toxicity of organic solvents, which poses a great safety hazard. It is generally recognized that the use of non-flammable, wide electrochemical window, and good mechanical properties of solid electrolytes (SEs) to replace the liquid organic electrolytes in traditional batteries is the best solution to solve their safety problems. To date, SEs can generally be divided into four categories: polymer electrolytes, oxide electrolytes, sulfide electrolytes, and halide electrolytes. Polymer electrolytes generally exhibit good mechanical softness and film-forming properties, but they face the problem of low room temperature ionic conductivity. Oxide electrolytes exhibit high ionic conductivity and a wide electrochemical window, but their brittle fracture characteristics and demanding high-temperature preparation conditions severely limit their practical applications. Sulfide electrolytes generally exhibit ultra-high ionic conductivity comparable to liquid electrolytes, and have the advantages of soft texture and cold pressing, but their narrow electrochemical window and poor air stability limit their large-scale application. In contrast, halide-based solid electrolytes (such as Li2ZrCl6, Na2ZrCl6, etc.) can combine the strong deformation ability of sulfides and the high-voltage resistance of oxides, and show great advantages in terms of raw material costs, so they are expected to promote the practical application of solid-state batteries. At present, lithium and sodium ion halide-based solid electrolytes (taking typical zirconium-based chloride solid electrolytes as an example) still face core problems such as insufficient ionic conductivity, poor compatibility with alkali metal negative electrodes, and easy water absorption and deliquescence leading to structural failure, which seriously limit the effective ion transition, interface stability and industrial adaptability. Therefore, the design and development of halide-based solid electrolyte systems with high ionic conductivity, stable compatibility with metal negative electrode interfaces and strong moisture resistance are of great significance to promote the practical application of alkali metal solid-state batteries. Summary of the invention

[0003] The object of the present invention is to provide an alkali metal ion oxychloride-based solid electrolyte material and a solid-state battery.

[0004] An alkali metal ion oxychloride-based solid electrolyte, characterized in that the structural formula of the oxychloride solid electrolyte is: 2-2x Zr 1-x M 2x Cl 6-6x O 3x ; Wherein, A is a monovalent alkali metal element Li, Na; M is a metal or lanthanide element In, Bi, Sb, Ce, La; the value range of x is: 0<x≤0.3.

[0005] Furthermore, the room temperature ionic conductivity of the electrolyte is greater than 0.08 mS / cm.

[0006] According to the method for preparing the oxychloride-based solid electrolyte material as described above, it is characterized by comprising:

[0007] According to the stoichiometric ratio of the general electrolyte structure formula, the precursors ACl (A=Li, Na), ZrCl4 and M2O3 (M=In, Bi, Sb, Ce, La) are weighed and mixed and ball-milled at room temperature under an inert atmosphere to obtain alkali metal ion oxychloride solid electrolyte powder.

[0008] Furthermore, the ball milling speed is 500-700 rpm; the ball milling time is 10-20 h; and the mass ratio of the precursor mixture to the ball milling beads is 1:(20-40).

[0009] Furthermore, the ball milling speed is preferably 600 rpm, and the ball milling time is preferably 15 to 20 h; and the preferred mass ratio of the precursor mixture to the ball milling beads is 1:30.

[0010] An alkali metal ion oxychloride solid electrolyte prepared according to the method as described above is applied to a solid-state battery, characterized in that the solid electrolyte can be used to prepare a solid electrolyte in an alkali metal (lithium, sodium) ion solid-state battery, and can also be used to prepare a composite positive and negative electrode additive; the alkali metal ion solid-state battery includes all-solid-state, quasi-solid-state and semi-solid-state batteries.

[0011] The key point of the present invention is that: after repeated experiments and explorations by the research team,

[0012] 1. Use oxychloride solid electrolytes to replace liquid organic electrolytes in traditional batteries. They are safe, reliable, and have good mechanical properties. Compared with lithium and sodium ion halide-based solid electrolytes, they have high ionic conductivity, good compatibility with alkali metal negative electrodes, and are not easy to absorb water and deliquesce. The introduction of metal cations in the structure can form alkali metal cation vacancies, regulate the site distribution of cations in the material lattice and the unit cell volume, and further play a role in reducing the carrier migration energy barrier and broadening the ion transmission channel. The divalent O anions mainly occupy part of the Cl sites and cause the increase of the electrolyte amorphization degree and the anion mixing disorder, thereby achieving effective regulation of the electrolyte phase composition and local microstructure. In addition, O 2- Doping can form a stronger bond with the central metal element Zr, improve the material's stability to moisture, and help improve the (electro)chemical stability of the electrolyte. The above characteristics lead to the production of A with high ionic conductivity, (electro)chemical stability and high moisture resistance. 2-2x Zr 1-x M 2x Cl6-6x O 3x Solid electrolyte materials.

[0013] 2. With low-priced Zr 4+ As the central metal ion in the oxychloride electrolyte, it has the characteristics of simple synthesis process, easy large-scale preparation and low cost.

[0014] 3. Through the metal oxide dual-doping strategy, an alkali metal ion oxychloride-based solid electrolyte with high ionic conductivity, good (electro)chemical stability and low price was prepared, which effectively improved the electrochemical performance of solid-state lithium and sodium ion batteries.

[0015] Compared with the prior art, the beneficial effects of the present invention are mainly embodied in:

[0016] 1. The alkali metal ion oxychloride-based solid electrolyte of the present invention can be prepared by conventional mechanical ball milling, and can be prepared by using low-cost Zr 4+ As the central metal ion in the oxychloride electrolyte, it has the advantages of simple synthesis process, easy large-scale preparation and low cost.

[0017] 2. Starting from the material structure design, the present invention prepares the above-mentioned alkali metal ion oxychloride-based solid electrolyte with high ionic conductivity, good (electro)chemical stability and low price through a metal oxide dual-doping strategy, thereby effectively improving the electrochemical performance of solid-state lithium and sodium ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 The Li prepared by ball milling in Example 1 (a) of the present invention is 1.6 Zr 0.8 In 0.4 Cl 4.8 O 0.6 The lithium ion oxychloride solid electrolyte and the Na 1.6 Zr 0.8 Bi 0.4 Cl 4.8 O 0.6 X-ray diffraction pattern of type sodium ion oxychloride solid electrolyte;

[0019] Figure 2 The Li prepared by ball milling in Example 1 (a) and Example 2 (b) of the present invention is 1.6 Zr 0.8 In 0.4 Cl 4.8 O 0.6 Type and Na 1.6 Zr 0.8 Bi 0.4 Cl 4.8 O0.6 Scanning electron microscope image of type alkali metal ion oxychloride solid electrolyte;

[0020] Figure 3 The Li prepared by ball milling in Example 1 (a) and Example 2 (b) of the present invention is 2-2x Zr 1-x M 2x Cl 6-6x O 3x (M is In, x=0.1, 0.2, 0.3) type and Na 2-2x Zr 1-x M 2x Cl 6-6x O 3x Electrochemical impedance spectroscopy of (M is Bi, x = 0.1, 0.2, 0.3) type lithium and sodium ion oxychloride solid electrolytes;

[0021] Figure 4 ab shows the Li obtained based on Example 1-2 of the present invention 1.6 Zr 0.8 In 0.4 Cl 4.8 O 0.6 and Na 1.6 Zr 0.8 Bi 0.4 Cl 4.8 O 0.6 Schematic diagram of charge and discharge curves of all-solid-state batteries as composite cathode electrolyte materials and electrolyte layers;

[0022] Figure 5 ab are X-ray diffraction patterns of Li2ZrCl6 and Na2ZrCl6 solid electrolyte materials in the comparative example;

[0023] Figure 6 ab are the electrochemical impedance spectra of Li2ZrCl6 and Na2ZrCl6 solid electrolyte materials in the comparative example. DETAILED DESCRIPTION

[0024] The following will be described in more detail with reference to a schematic diagram of an alkali metal ion oxychloride-based solid electrolyte of the present invention and its preparation method and application, wherein a preferred embodiment of the present invention is shown, and it should be understood that those skilled in the art can modify the present invention described herein, while still achieving the advantageous effects of the present invention. Therefore, the following description should be understood as a broad guide for those skilled in the art, and not as a limitation of the present invention.

[0025] The general structural formula of an alkali metal ion oxychloride solid electrolyte is: 2-2x Zr 1-x M 2x Cl6-6x O 3x ; Wherein, A is a monovalent alkali metal element Li, Na; M is a metal or lanthanide element In, Bi, Sb, Ce, La; the value range of x is: 0<x≤0.3.

[0026] A method for preparing an alkali metal ion oxychloride solid electrolyte comprises the following steps and conditions:

[0027] 1) According to the stoichiometric ratio of the general formula, the precursors ACl (A = Li, Na), ZrCl4 and M2O3 (M = In, Bi, Sb, Ce, La) are weighed and mixed and ball-milled at room temperature to obtain a solid electrolyte powder.

[0028] 2) The ball milling speed is 500-700 rpm, preferably 600 rpm. The ball milling time is 10-20 h, preferably 15-20 h. The mass ratio of the precursor mixture to the ball milling beads is 1: (20-40), preferably 1:30.

[0029] In the synthesis process of the alkali metal ion oxychloride-based solid electrolyte of the present invention, the precursor materials ACl (A = Li, Na), ZrCl4 and M2O3 (M = In, Bi, Sb, Ce, La) are weighed respectively according to the stoichiometric ratio and the solid electrolyte material is prepared under high-speed mechanical ball milling mixing reaction. Among them, the introduction of metal cations in the structure can form alkali metal cation vacancies, regulate the site distribution and unit cell volume of cations in the material lattice, and further play a role in reducing the carrier migration energy barrier and widening the ion transmission channel. The divalent O anions mainly occupy part of the Cl sites and cause the increase of the electrolyte amorphization degree and the anion mixing disorder, thereby realizing the effective regulation of the electrolyte phase composition and local microstructure. In addition, O 2- Doping can form a stronger bond with the central metal element Zr, improve the material's stability to moisture, and help improve the (electro)chemical stability of the electrolyte. The above characteristics lead to the production of A with high ionic conductivity, (electro)chemical stability and high moisture resistance. 2-2x Zr 1-x M 2x Cl 6-6x O 3x Solid electrolyte materials.

[0030] The alkali metal ion oxychloride-based solid electrolyte of the present invention is mainly used for preparing solid electrolytes or composite positive and negative electrode additives of solid-state alkali metal ion batteries (including all-solid-state, quasi-solid-state and semi-solid-state batteries).

[0031] Embodiment 1: Embodiment of the present invention is Li 2-2x Zr 1-x M 2x Cl 6-6x O3x Preparation and electrochemical performance of (M is In, x=0.1, 0.2, 0.3) type lithium ion oxychloride solid electrolyte materials.

[0032] In a glove box filled with argon, weigh the following:

[0033] (1) Li 1.8 Zr 0.9 In 0.2 Cl 5.4 O 0.3 : 0.381 g LiCl + 1.049 g ZrCl4 + 0.278 g In2O3;

[0034] (2) Li 1.6 Zr 0.8 In 0.4 Cl 4.8 O 0.6 : 0.339 g LiCl + 0.932 g ZrCl4 + 0.555 g In2O3;

[0035] (3) Li 1.4 Zr 0.7 In 0.6 Cl 4.2 O 0.9 : 0.297 g LiCl + 0.816 g ZrCl4 + 0.833 g In2O3;

[0036] The above raw materials with different mass ratios were added into a ball mill and zirconium dioxide ball milling beads were added. The ball milling beads had a diameter of 2 to 10 mm and a ball-to-material ratio of 30:1. The ball milling was performed in an inert atmosphere planetary ball mill at a speed of 600 rpm for 15 h. After the ball milling, the prepared solid electrolyte sample was transferred to an agate mortar and ground for 30 min until the powder particle diameter was uniformly distributed, and finally a lithium ion oxychloride solid electrolyte powder sample with the corresponding chemical formula was obtained.

[0037] Figure 1 a is the Li prepared in this example 1.6 Zr 0.8 In 0.4 Cl 4.8 O 0.6 X-ray diffraction patterns of solid electrolyte materials, Figure 1 a characteristic peak comparison shows that the synthesized Li 1.6 Zr 0.8 In 0.4 Cl 4.8 O 0.6Lithium ion oxychloride solid electrolyte powder is a crystalline material with low crystallinity and has a crystal structure similar to Li3YCl6. It belongs to the trigonal system and has a space group of .

[0038] Figure 2 a is the Li prepared in this example 1.6 Zr 0.8 In 0.4 Cl 4.8 O 0.6 Scanning electron microscope images of materials, from Figure 2 As can be seen in a, the particle diameter of the synthesized lithium ion oxychloride solid electrolyte powder is distributed in the range of 1 to 10 μm.

[0039] Figure 3 a is the Li prepared in this example 2-2x Zr 1-x In 2x Cl 6-6x O 3x Electrochemical impedance spectroscopy of (x=0.1, 0.2, 0.3) type lithium ion oxychloride solid electrolyte. According to the formula σ = L / R·S, Li 2-2x Zr 1- x In 2x Cl 6-6x O 3x The ionic conductivity of the (x=0.1, 0.2, 0.3) type lithium-based oxychloride solid electrolyte increases first and then decreases with the increase of In2O3 doping amount. 1.6 Zr 0.8 In 0.4 Cl 4.8 O 0.6 When the room temperature ionic conductivity reaches the maximum value of 1.1 mS / cm, the room temperature ionic conductivity of other ratios is Li 1.8 Zr 0.9 In 0.2 Cl 5.4 O 0.3 (0.82 mS / cm) and Li 1.4 Zr 0.7 In 0.6 Cl 4.2 O 0.9 (0.63 mS / cm).

[0040] Embodiment 2: Embodiment of the present invention is Na 2-2x Zr 1-x M 2x Cl 6-6x O 3xPreparation and electrochemical performance study of (M is Bi, x=0.1, 0.2, 0.3) type sodium ion oxychloride solid electrolyte materials.

[0041] In a glove box filled with argon, weigh the following:

[0042] (1) Na 1.8 Zr 0.9 Bi 0.2 Cl 5.4 O 0.3 : 0.526 g NaCl + 1.049 g ZrCl4 + 0.466 g Bi2O3;

[0043] (2) Na 1.6 Zr 0.8 Bi 0.4 Cl 4.8 O 0.6 : 0.468 g NaCl + 0.932 g ZrCl4 + 0.932 g Bi2O3;

[0044] (3) Na 1.4 Zr 0.7 Bi 0.6 Cl 4.2 O 0.9 : 0.409 g NaCl + 0.816 g ZrCl4 + 1.398 g Bi2O3;

[0045] The above raw materials with different mass ratios were added into a ball mill and zirconium dioxide ball milling beads were added. The ball milling beads had a diameter of 2 to 10 mm and a ball-to-material ratio of 30:1. The ball milling was performed in an inert atmosphere planetary ball mill with a ball milling speed of 600 rpm and a ball milling time of 15 h. After the ball milling, the prepared solid electrolyte sample was transferred to an agate mortar and ground for 30 min until the powder particle diameter was uniformly distributed, and finally a sodium ion oxychloride solid electrolyte powder sample with the corresponding chemical formula was obtained.

[0046] Figure 1 b is the Na prepared in this example 0.8 Zr 0.4 Bi 1.2 Cl 2.4 O 1.8 The X-ray diffraction pattern of the material is Figure 1 b characteristic peak comparison shows that the synthesized Na 0.8 Zr 0.4 Bi 1.2 Cl 2.4 O 1.8The sodium ion oxychloride solid electrolyte powder material is a crystalline material with low crystallinity and has a crystal structure similar to that of Li3YCl6. It belongs to the trigonal system and has a space group of .

[0047] Figure 2 b is the Na prepared in this example 0.8 Zr 0.4 Bi 1.2 Cl 2.4 O 1.8 Scanning electron microscope images of materials, from Figure 2 As can be seen in b, the particle diameter of the synthesized sodium ion oxychloride solid electrolyte powder is distributed in the range of 1 to 10 μm.

[0048] Figure 3 b is the Na prepared in this example 2-2x Zr 1-x Bi 2x Cl 6-6x O 3x Electrochemical impedance spectroscopy of (x=0.1, 0.2, 0.3) type sodium ion oxychloride solid electrolyte. According to the formula σ = L / R·S, Na 2-2x Zr 1- x Bi 2x Cl 6-6x O 3x The sodium ion conductivity of the (x=0.1, 0.2, 0.3) type sodium-based oxychloride solid electrolyte increases first and then decreases with the increase of Bi2O3 doping amount. 1.6 Zr 0.8 Bi 0.4 Cl 4.8 O 0.6 When the room temperature ionic conductivity reaches the maximum value of 0.24 mS / cm, the room temperature ionic conductivity of other ratios is Na 1.8 Zr 0.9 Bi 0.2 Cl 5.4 O 0.3 (0.16 mS / cm) and Na 1.4 Zr 0.7 Bi 0.6 Cl 4.2 O 0.9 (0.086 mS / cm).

[0049] Embodiment three:

[0050] An embodiment of the present invention provides a secondary battery comprising the lithium ion oxychloride solid electrolyte material;

[0051] The preparation method of the secondary battery is as follows:

[0052] LiNi was prepared in an argon-filled glove box. 0.8 Co 0.1 Mn 0.1 O2, VGCF and the lithium ion oxychloride solid electrolyte material Li prepared in Example 1 1.6 Zr 0.8 In 0.4 Cl 4.8 O 0.6 The composite positive electrode was prepared by mixing at a mass ratio of 70:5:30, and then 100 mg Li 1.6 Zr 0.8 In 0.4 Cl 4.8 O 0.6 The tablets were pressed in a battery mold at a pressure of 300 MPa, 10 mg of composite positive electrode was added to one side of the electrolyte, and the pressure was maintained at 370 MPa for 2 minutes. Then, a metal lithium foil negative electrode with a diameter of 9 mm was added to the other side of the electrolyte, and the tablets were cold-pressed and fixed at a pressure of 1 MPa for subsequent related electrochemical performance tests.

[0053] The assembled secondary battery was tested with a constant current charge and discharge test in the voltage range of 2.7 to 4.2 V using the Blue Electric Battery Test System. The charge and discharge rate was 0.1 C. The charge and discharge curves of the battery in the first week are shown in the figure below. Figure 4 As shown in a.

[0054] The first cycle coulombic efficiency of the secondary battery obtained in the embodiment of the present invention can reach 89.4%, and the discharge specific capacity is 153 mAh g -1 .

[0055] Embodiment 4:

[0056] An embodiment of the present invention provides a secondary battery comprising the sodium ion oxychloride solid electrolyte material;

[0057] The preparation method of the secondary battery is as follows:

[0058] In a glove box filled with argon, Na3V2(PO4)3, VGCF and the sodium ion oxychloride solid electrolyte material Na prepared in Example 2 were added. 0.8 Zr 0.4 Bi 1.2 Cl 2.4 O 1.8 The composite positive electrode was prepared by mixing at a mass ratio of 70:5:30, and then 100 mg Na 0.8 Zr 0.4 Bi 1.2 Cl 2.4 O 1.8The tablets were pressed in a battery mold at a pressure of 300 MPa, 10 mg of the composite positive electrode was added to one side of the electrolyte, and the pressure was maintained at 370 MPa for 2 minutes. Then, a metal sodium foil negative electrode with a diameter of 9 mm was added to the other side of the electrolyte, and the tablets were cold-pressed and fixed at a pressure of 1 MPa for subsequent related electrochemical performance tests.

[0059] The assembled secondary battery was tested with a constant current charge and discharge test in the voltage range of 2 to 3.8 V using the Blue Electric Battery Test System. The charge and discharge rate was 0.1 C. The charge and discharge curves of the battery in the first week are shown in the figure. Figure 4 As shown in b.

[0060] The first cycle coulombic efficiency of the secondary battery obtained in the embodiment of the present invention can reach 93.8%, and the reversible specific capacity is 86.8 mAh g -1 .

[0061] Comparative Example 1:

[0062] The comparative example of the present invention provides a lithium ion halide solid electrolyte material Li2ZrCl6;

[0063] The preparation method of the lithium ion halide solid electrolyte material Li2ZrCl6 comprises the following steps: in a glove box, anhydrous LiCl and ZrCl4 are weighed and mixed at a stoichiometric ratio of 2:1, and then poured into a ball milling jar, the ball diameter is 2 to 10 mm, and the ball-to-material ratio is 30:1. The ball milling is performed in an inert atmosphere planetary ball mill, the ball milling speed is 600 rpm, and the ball milling time is 15 h. After the ball milling is completed, the prepared solid electrolyte sample is transferred to an agate mortar and ground for 30 min until the powder particle diameter is evenly distributed, and finally a Li2ZrCl6 electrolyte powder sample is obtained.

[0064] Figure 5 a is the X-ray diffraction spectrum of the Li2ZrCl6 electrolyte material obtained in the comparative example, Figure 5 It can be seen from the comparison of characteristic peaks that the synthesized Li2ZrCl6 solid electrolyte powder material is a crystalline material with low crystallinity and has a crystal structure similar to that of Li3YCl6, belonging to the trigonal system, and the space group is .

[0065] Figure 6 a is the AC impedance test spectrum of the Li2ZrCl6 electrolyte material obtained in the comparative example. According to the formula σ =L / R·S, it can be calculated that the room temperature ionic conductivity of the Li2ZrCl6 electrolyte material obtained in the present invention is 0.39 mS / cm.

[0066] Comparative Example 2:

[0067] The comparative example of the present invention provides a sodium ion halide solid electrolyte material Na2ZrCl6;

[0068] The preparation method of the sodium ion halide solid electrolyte material Na2ZrCl6 comprises the following steps: in a glove box, anhydrous NaCl and ZrCl4 are weighed and mixed at a stoichiometric ratio of 2:1, and then poured into a ball milling jar, the ball diameter is 2 to 10 mm, and the ball-to-material ratio is 30:1. The ball milling is performed in an inert atmosphere planetary ball mill, the ball milling speed is 600 rpm, and the ball milling time is 15 h. After the ball milling is completed, the prepared solid electrolyte sample is transferred to an agate mortar and ground for 30 min until the powder particle diameter is evenly distributed, and finally a Na2ZrCl6 electrolyte powder sample is obtained.

[0069] Figure 5 b is the X-ray diffraction spectrum of the Na2ZrCl6 electrolyte material obtained in the comparative example. Figure 5 b Characteristic peak comparison shows that the synthesized Na2ZrCl6 solid electrolyte powder material is a crystalline material with low crystallinity and has a crystal structure similar to that of Li3YCl6, belonging to the trigonal system, with a space group of .

[0070] Figure 6 b is the AC impedance test spectrum of the Na2ZrCl6 electrolyte material obtained in the comparative example. According to the formula σ =L / R·S, it can be calculated that the room temperature ionic conductivity of the Na2ZrCl6 electrolyte material obtained in the present invention is 0.011 mS / cm.

[0071] It can be found from Examples 1-2 and Comparative Examples 1-2 that the alkali metal (lithium and sodium) ion oxychloride solid electrolyte material obtained by the technical solution of the present invention has significantly improved ionic conductivity; it can be further found from Examples 3-4 that the alkali metal ion oxychloride solid electrolyte material prepared by the technical solution of the present invention, when applied to the preparation of secondary battery composite electrodes, exhibits higher first-cycle coulombic efficiency and discharge capacity.

[0072] Finally, it is stated again that the above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any technician in the relevant technical field, without departing from the scope of the technical solution of the present invention, makes any form of equivalent replacement or modification to the technical solution and technical content disclosed in the present invention, which does not depart from the content of the technical solution of the present invention and still falls within the protection scope of the present invention.

Claims

1. An alkali metal ion oxychloride-based solid electrolyte, characterized in that: The general structural formula of oxychloride solid electrolyte is: 2-2x Zr 1-x M 2x Cl 6-6x O 3x ; Wherein, A is a monovalent alkali metal element Li, Na; M is a metal or lanthanide element In, Bi, Sb, Ce, La; the value range of x is: 0<x≤0.

3.

2. The oxychloride solid electrolyte according to claim 1, characterized in that The room temperature ionic conductivity of the electrolyte is greater than 0.08 mS / cm.

3. A method for preparing an oxychloride solid electrolyte material as claimed in claim 1 or 2, characterized in that: include: Precursors ACl (Li, Na), ZrCl4 and M2O3 (M = In, Bi, Sb, Ce, La) are weighed according to the stoichiometric ratio of the general electrolyte structure formula, and mixed and ball-milled with ball milling beads at room temperature under an inert atmosphere to obtain oxychloride solid electrolyte powder.

4. The method for preparing an oxychloride solid electrolyte material according to claim 3, characterized in that: The ball milling speed is 500-700 rpm; the ball milling time is 10-20 h; and the mass ratio of the precursor mixture to the ball milling beads is 1:(20-40).

5. The method for preparing an oxychloride solid electrolyte material according to claim 3 or 4, wherein: The ball milling speed is 600 rpm, the ball milling time is 15 to 20 h, and the mass ratio of the precursor mixture to the ball milling beads is 1:

30.

6. The oxychloride solid electrolyte prepared by the method according to claim 3 is applied to solid-state batteries, characterized in that: The solid electrolyte can be used to prepare the solid electrolyte in alkali metal (lithium, sodium) ion solid-state batteries, and can also be used to prepare composite positive and negative electrode additives; the alkali metal ion solid-state batteries include all-solid-state, quasi-solid-state and semi-solid-state batteries.

Citation Information

Patent Citations

  • Halide-based sodium ion solid electrolyte as well as preparation method and application thereof

    CN115566259A

  • Sodium ion halide solid electrolyte, preparation method and all-solid-state sodium ion battery

    CN118016986A

  • Chlorine oxide solid electrolyte as well as preparation method and application thereof

    CN118712468A

  • Oxidation halide solid electrolyte and preparation method and application thereof

    CN118748268A

  • Autoinjector having the function of injecting drug with the pain relief algorithm

    KR1020240163402A

Cited By

  • Low-cost oxide-chloride composite solid electrolyte material and preparation method and application thereof

    CN119764539A

  • Heteroanion oxyhalide solid electrolyte, preparation method and application thereof, and all-solid-state battery

    CN121484182A

  • Heteroanion oxyhalide solid-state electrolyte, preparation method, application and full solid-state battery thereof

    CN121484182B

  • All-solid-state secondary battery

    WO2026191004A1